Penyusunan Model Program Corporate Social Responsibility (CSR) di Perguruan Tinggi Kota Salatiga Dalam Upaya Meningkatkan Intake Perguruan Tinggi - Lina Sinatra Wijaya; Krismiyati Krismiyati (Jurnal Ekonomi dan Bisnis, 2014)
Corporate Social Responsibility (CSR) is one of the promotion techniques done by a Public Relations in higher education institutions to face the tougher competition among the higher education institution in gaining new students. Most higher education institutions in Salatiga try to do some CSR programs to achieve their goal. This study tries to investigate what suitable model of CSR done by higher education institutions in Salatiga-Central Java which is also implemented and the influence of this program to students’ intake in one academic year. Lastly, it tries to propose a CSR modeling for increasing students’ intake at higher education Institution in Salatiga-Central Java. This study employs interview and literature study for data collection. The data are then analyzed qualitatively to answer the posed research questions. This study involved 7 Higher education institutions in Salatiga-Central Java and also 19 High schools which are spread in 7 cities in Central Java. The result of the study shows that the Public Relations unit in each higher education institutions has carried out their CSR program to some of the Schools in Central Java, but lack of coordination done by both parties. However they emphasize their CSR program focusing on community service, high school student activities, scholarships and training. In order to effectively achieve the goal, an intake cycled relations model is proposed.